Audio technology and its influence on the rise of Colombian tropical music in the 60s and 70s through the creative role of the music producer (Revista Argentina de Musicología, 2022)
The music recorded by the main Colombian record companies established in Medellín between the 1960s and 1970s transcended musical history and remains in the cultural memory of not only Colombia, but also other Latin American countries. This was a time of great boom in the music business in the country, mainly in the traditional genres of the Caribbean coast performed by youth groups influenced by foreign music such as twist and rock and roll.The combination of artists, traditional music and the recording technology of that time was consolidated as the fundamental core of a sound that transcended the Colombian imaginary. Therefore, to obtain a pertinent musicological analysis according to Zagorski-Thomas (2014), the study of the development of audio technology and its use in record productions is essential. Hence the importance of determining the scope of the creative role played by the sound engineer, the recording technician and the music producer in their relationship with the performers and arrangers, according to Burgess (2013).Thus, a reflexive study is proposed to show the incidence of these factors, which allowed consolidating a particular sound and aesthetics in the boom of the tropical music industry in Medellín in the years mentioned.
Keywords: record production; Colombian tropical music; record industry; history of record production in Colombia